Fn14 and TNFR2 as regulators of cytotoxic TNFR1 signaling - Siegmund, Daniela; Zaitseva, Olena; Wajant, Harald (Frontiers in Cell and Developmental Biology, 2023)
Tumor necrosis factor (TNF) receptor 1 (TNFR1), TNFR2 and fibroblast growth factor-inducible 14 (Fn14) belong to the TNF receptor superfamily (TNFRSF). From a structural point of view, TNFR1 is a prototypic death domain (DD)-containing receptor. In contrast to other prominent death receptors, such as CD95/Fas and the two TRAIL death receptors DR4 and DR5, however, liganded TNFR1 does not instruct the formation of a plasma membrane-associated death inducing signaling complex converting procaspase-8 into highly active mature heterotetrameric caspase-8 molecules. Instead, liganded TNFR1 recruits the DD-containing cytoplasmic signaling proteins TRADD and RIPK1 and empowers these proteins to trigger cell death signaling by cytosolic complexes after their release from the TNFR1 signaling complex. The activity and quality (apoptosis versus necroptosis) of TNF-induced cell death signaling is controlled by caspase-8, the caspase-8 regulatory FLIP proteins, TRAF2, RIPK1 and the RIPK1-ubiquitinating E3 ligases cIAP1 and cIAP2. TNFR2 and Fn14 efficiently recruit TRAF2 along with the TRAF2 binding partners cIAP1 and cIAP2 and can thereby limit the availability of these molecules for other TRAF2/cIAP1/2-utilizing proteins including TNFR1. Accordingly, at the cellular level engagement of TNFR2 or Fn14 inhibits TNFR1-induced RIPK1-mediated effects reaching from activation of the classical NFκB pathway to induction of apoptosis and necroptosis. In this review, we summarize the effects of TNFR2- and Fn14-mediated depletion of TRAF2 and the cIAP1/2 on TNFR1 signaling at the molecular level and discuss the consequences this has in vivo.